Species of Wadicosa (Araneae, Lycosidae): a new species from Madagascar - Kronestedt, Torbjörn (Zootaxa, 2017)
Since establishing the wolf spider genus Wadicosa Zyuzin, 1985 (Zyuzin 1985), eleven species have been accepted in it, either by transfer from Lycosa Latreille, 1804 or Pardosa C.L. Koch, 1847 or by original designation (WSC 2017). However, according to Kronestedt (1987), additional species wait to be formally transferred to Wadicosa. The genus is restricted to the Old World, with one species, Wadicosa jocquei Kronestedt, 2015, recently described from Madagascar and surrounding islands.